PROMISING DIAGNSOTIC MARKER AT NICU AND PICU-NEW APPRROACHES FOR DIAGNOSTIC AND TREATMENT - Sofijanova, Aspazija; Timovska Naunova, Silvana; Mangjukovska-Bicevska, Hristina; Kimovska-Hristova, Mica; Voinovska, Tamara; Jordanova, Olivera; Bojagjieva, Sonja; Neskova, Spasija; Kirovski, Ilija (Journal of Morphological Sciences; Vol 2 No 2 (2019): JMS, 2019)
The aim of this study  is evaluate the initial   PCT   levels on the outcome of patients in pediatric intensive care units and find out if these biomarker can be used to predict sepsis. The study was designed as a prospective, clinical, investigation conducted in the period sixth months, which included 45 (M:F=25:20) newborns with two or three clinical signs of sepsis hospitalized in the Intensive  Care Unit at the PHI University Clinic for Children Diseases.  The patient  have been divided into two groups: I group included 31 septic newborns with negative blood culture and II group - 14 septic newborns with positive blood cultures. Results of blood count (WBC), CRP and PCT, were recorded. Procalcitonin PCT  levels at first 24 hours of the admission were increased in all 45 newborns (â‰¥2 ng/mL). The values of C-reactive protein gradually increase after 12-36 hours at admission. The second measurement, after 3 days usage of an adequate antibiotic treatment, the levels of PCT is decreased,regardless of whether blood culture is positive or negative, except 5 patients develop severe sepsis, and three patients develop septic shock. After the third measurement the levels of PCT and CRP is decreased. NIV was used in  39.8% patients and Invasive MV was used in  29.8% patients.Sensitivity of procalcitonin 83.5%, Specificity of procalcitonin 81.3%. Procalcitonin value  is a early prognostic factor for sepsis and it is a reliable parameter whether an appropriate antibiotic for the treatment is used,thus increasing newborns safety,and reducing costs .